PENGARUH HARGA SAHAM, TRADING VOLUME ACTIVITY DAN RISIKO SAHAM TERHADAP BID-ASK SPREAD (Studi pada Perusahaan LQ-45 di Bursa Efek Jakarta) - Istanti, Lulu Nurul (Jurnal Ekonomi Modernisasi, 2009)
This study aimed to analyze the effect of stock price, shares of Tradimg volume activity and the risk of bid-ask spread. And test them with statistical tools. This study argued that share price, TVA and risk affect the stock bid-ask spread partially or together. For this purpose, we used multiple regression analysis. Samples taken are the LQ-45 firms listed on the JSE the period February 2002 until July 2005. The results showed that the Trading volume activity and risk affect the stock bid-ask spread, while stock prices are not. And jointly share price, Ttading volume activity and risk affect the stock bid-ask spread